2021
DOI: 10.1038/s41598-021-98202-6
|View full text |Cite
|
Sign up to set email alerts
|

Performance of individual dietary diversity score to identify malnutrition among patients living with HIV in Ethiopia

Abstract: There is a lack of uniformity in developing and validating indicators of nutritional status among People Living with Human Immunodeficiency Virus (PLHIV). Experiences from low and middle-income countries are scant, and differences in methodological and analytical approaches affect the comparability and generalizability of findings. Therefore, this study investigated the performance of individual diversity score (IDDS) as a proxy indicator of nutritional status among PLHIV. We conducted a facility-based cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
3
5
0
Order By: Relevance
“…Similar results were obtained in prior studies conducted in Bangladesh and China (Rahman et al, 2020a;Sujan et al, 2021). There may be more crowded people and greater access to media and health information leading to higher risks of COVID-19-related fear among urban diabetes patients (Huang et al, 2021;World Economic Forum., 2022). Our study also showed that diabetes people who engaged in regular MVPA in recommended level had decreased probability of fear related to COVID-19, compared to those who did not exercise.…”
Section: Participant's Characteristicssupporting
confidence: 81%
“…Similar results were obtained in prior studies conducted in Bangladesh and China (Rahman et al, 2020a;Sujan et al, 2021). There may be more crowded people and greater access to media and health information leading to higher risks of COVID-19-related fear among urban diabetes patients (Huang et al, 2021;World Economic Forum., 2022). Our study also showed that diabetes people who engaged in regular MVPA in recommended level had decreased probability of fear related to COVID-19, compared to those who did not exercise.…”
Section: Participant's Characteristicssupporting
confidence: 81%
“…This study showed that self-reported HIV status was strongly associated with being underweight ( P = 0.000) among CFSWs. Sex workers with positive HIV status had a 21.6-times higher odds ratio to being underweight than HIV-negative CFSWs, which agrees with recent studies ( Hussien et al., 2021 ; Nigusso & Mavhandu-Mudzusi, 2021 ). A higher prevalence of malnutrition among people living with HIV and AIDS (PLWHA) is reported in Ethiopia ( Hussien et al., 2021 ; Nigusso & Mavhandu-Mudzusi, 2021 ), which also observed in this study as a strong predictor of undernutrition among HIV-positive sex workers.…”
Section: Discussionsupporting
confidence: 91%
“…Sex workers with positive HIV status had a 21.6-times higher odds ratio to being underweight than HIV-negative CFSWs, which agrees with recent studies ( Hussien et al., 2021 ; Nigusso & Mavhandu-Mudzusi, 2021 ). A higher prevalence of malnutrition among people living with HIV and AIDS (PLWHA) is reported in Ethiopia ( Hussien et al., 2021 ; Nigusso & Mavhandu-Mudzusi, 2021 ), which also observed in this study as a strong predictor of undernutrition among HIV-positive sex workers. This finding is also supported by the qualitative part of this study, which found that ‘sexually transmitted infections/STIs’, and HIV are the most common illness among malnourished CFSWs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The reliability of the overall questionnaires was checked by Cronbach’s α and showed 0.66. The validity and reliability test for tools to screen for depression and dietary diversity score was checked by other studies conducted in Ethiopia and found sensitivity(88%), specificity(78%) and Cronbach’s α = 0.78 for depression and sensitivity(88%), specificity(71%) and Cronbach’s α = 0.76 for dietary diversity score [ 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%